Cohen-Cole: The Open Mind - Christian, Dayé (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
Book review of: Cohen-Cole, Jamie (2014) The Open Mind: Cold War Politics and the Sciences of Human Nature. Chicago, London: The University of Chicago Press. 368 pp. ISBN: 978-0-226-09216-4. Price: $ 48,00 (Cloth)